Relation of Myocardial Blood Flow and Initial Cardiac Uptake of 15-(p-123I-Phenyl)-Pentadecanoic Acid in the Canine Heart - Reske, S. N.; Schön, S.; Knust, E. J.; Machulla, H.-J.; Eichelkraut, W.; Hahn, N.; Winkler, C. (Nuklearmedizin - NuclearMedicine, 1984)
In 8 pentobarbital-anaesthetized mongrel dogs the correlation between regional myocardial blood flow (RMBF) and regional cardiac uptake of 15-(p-123I-phenyl)-pentadecanoic acid (IPPA) was determined. Three animals were studied under control conditions, in three dogs an acute ischemia was produced by LAD ligation, and two dogs were paced at 195 beats/min. RMBF values were 20–50 ml/min-100 g in acutely ischemic myocardium. 90–120 ml/ min·100 g under normal conditions and 200–250 ml/min·100 g during pacing-induced stimulation. Total cardiac uptake of IPPA was 4.5–6% of the injected dose. In normal and acutely ischemic myocardium a good correlation between RMBF and IPPA uptake was obtained. Under stimulated conditions only a moderate increase of IPPA accumulation was found. At RMBF values above 150–170 ml/ min·100 g an upper limit of IPPA uptake was observed and can be explained by limited diffusion or an increased utilization of alternative substrates.